Principles of auditing and other assurance services - Whittington, Ray (McGraw-Hill/Irwin, 2014)
Includes bibliographical references and index; The role of the public accountant in the American economy -- Professional standards -- Professional ethics -- Legal liability of CPAs -- Audit evidence and documentation -- Planning the audit; linking audit procedures to risk -- Internal control -- Consideration of internal control in an information technology environment -- Audit sampling -- Cash and financial investments -- Accounts receivable, notes receivable, and revenue -- Inventories and cost of goods sold -- Property, plant, and equipment: depreciation and depletion -- Accounts payable and other liabilities -- Debt and equity capital -- Auditing operations and completing the audit -- Auditors' report -- Integrated audits of public companies -- Additional assurance services: historical financial information -- Additional assurance services: other information -- Internal, operational, and compliance auditing